Kinerja Guru SMP Negeri 6 Kota Bekasi dipengaruhi oleh Disiplin Kerja melalui Lingkungan Kerja - Vidia Novianti; Eddy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
This study aims to determine the performance of teachers at SMP Negeri 6 Bekasi City is influenced by work discipline through the work environment. The research method used is a quantitative approach. The population in the study were teachers at SMP Negeri 6 Bekasi City using a general sample, namely all members of the population were sampled. The analysis method used path analysis. The results of the study indicate that 1) Work discipline has a significant effect on teacher performance; 2) The work environment has a significant effect on teacher performance; 3) Work discipline has a significant effect on the work environment; and 4) Teacher performance is not affected by work discipline through the work environment.